Spontaneous activity of astrocytes is a stochastic functional signal for memory consolidation - Gabriele Losi; Beatrice Vignoli; Rocco Granata; Annamaria Lia; Micaela Zonta; Gabriele Sansevero; Francesca Pischedda; Angela Chiavegato; Spartaco Santi; Lorena Zentilin; Nicoletta Berardi; Gian Michele Ratto; et al. (Proceedings of the National Academy of Sciences, 2025)
In the absence of explicit neuronal inputs, the glial cell astrocytes exhibit recurring intracellular Ca 2+ fluctuations, primarily localized at thin processes, known as Ca 2+ microdomains (MDs). Although spontaneous Ca 2+ MDs are present throughout the brain, their putative role is unknown. Here, we question whether, owing to their recurring signaling mode, spontaneous Ca 2+ MDs contribute to slowly evolving phenomena in the brain, such as memory consolidation. We demonstrate that, in the perirhinal cortex, a central region in recognition memory, these events promote Ca 2+ -dependent gliotransmission and modulate synaptic strengthening. Their recurring activity extends the release of the gliotransmitter brain-derived neurotrophic factor (BDNF) over time, ensuring the sustained Tropomyosin Receptor Kinase B (TrkB)-signaling required for the consolidation of long-term synaptic potentiation and lasting memories. We also show that Ca 2+ MDs, which are stochastic events, preserve their random behavior during gliotransmission, introducing an element of unpredictability into the process of memory retention. Our study assigns to spontaneous, stochastic activity in astrocytes a unique functional role in shaping and stabilizing memory circuits.